Exploration of topological optimization capabilities of ANSYS Workbench - Thiruchelvam Rajnivas (Nanyang Technological University, 2024)
This Final Year Project (FYP) delves into topological optimization using ANSYS Workbench, aiming to enhance engineering design by minimizing material usage while ensuring structural robustness. Motivated by the complexities of traditional optimization methods, this project focuses on ANSYS Workbench as a user-friendly platform for topology optimization, despite its inherent challenges. The software has many different parameters that can be adjusted leading to varying results. Therefore, the objective is to develop a systematic methodology for optimization, encompassing problem definition, shape optimization for given objectives, and optimization with fixed response constraints. Features in ANSYS Workbench such as SpaceClaim for geometry creation, meshing techniques, static structural analysis, and topological optimization are explored. The optimization framework developed in this FYP will be used to test on various geometries with varying objectives and response constraints. The results from this project are expected to be useful for engineers to design better structures with improved performance, reliability, and cost-effectiveness.